The acoustic and perceptual cues affecting melody segregation for listeners with a cochlear implant - Marozeau, Jeremy; Innes-Brown, Hamish; Blamey, Peter J. (Frontiers in Psychology, 2013)
Our ability to listen selectively to single sound sources in complex auditory environments is termed ‘auditory stream segregation.’ This ability is affected by peripheral disorders such as hearing loss, as well as plasticity in central processing such as occurs with musical training. Brain plasticity induced by musical training can enhance the ability to segregate sound, leading to improvements in a variety of auditory abilities. The melody segregation ability of 12 cochlear-implant recipients was tested using a new method to determine the perceptual distance needed to segregate a simple 4-note melody from a background of interleaved random-pitch distractor notes. In experiment 1, participants rated the difficulty of segregating the melody from distracter notes. Four physical properties of the distracter notes were changed. In experiment 2, listeners were asked to rate the dissimilarity between melody patterns whose notes differed on the four physical properties simultaneously. Multidimensional scaling analysis transformed the dissimilarity ratings into perceptual distances. Regression between physical and perceptual cues then derived the minimal perceptual distance needed to segregate the melody. The most efficient streaming cue for CI users was loudness. For the normal hearing listeners without musical backgrounds, a greater difference on the perceptual dimension correlated to the temporal envelope is needed for stream segregation in CI users. No differences in streaming efficiency were found between the perceptual dimensions linked to the F0 and the spectral envelope. Combined with our previous results in normally-hearing musicians and non-musicians, the results show that differences in training as well as differences in peripheral auditory processing (hearing impairment and the use of a hearing device) influences the way that listeners use different acoustic cues for segregating interleaved musical streams.